Examining Gender Divide, Reading Habits and Preferences in EFL Undergraduate Students - Arifin, Riyadh Ahsanul; Sakina, Rahma; Mustika, Rispa; Putri, Wulandari (Ma'soem University, 2025)
This study explores gender differences, reading habits, and preferences among undergraduate students studying English as a Foreign Language (EFL) at Ma'soem University, focusing on second, fourth, and eighth semesters. A qualitative descriptive approach was used to gather detailed data through comprehensive questionnaires and in-depth interviews. The sample included 32 participants, evenly distributed between male and female students. Key findings revealed a significant language preference gap, with 37.5% of female students preferring foreign language reading, compared to 18.8% of males who favored their native language. Regarding format, male students overwhelmingly preferred print books (93.8%), while females were more divided, with 75% favoring print and 25% choosing electronic formats. Both genders leaned towards fiction, though females showed a slightly stronger preference. Genre preferences also differed, with males favoring fantasy, mystery/thriller, and self-help, while females leaned towards fantasy, romance, and self-help. Access methods varied, with males more likely to use bookstores and lending networks, while females frequently used libraries and online platforms.